2014
DOI: 10.1021/jf405329e
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ROS-Dependent Mitochondria-Mediated Intrinsic Apoptosis in MDA-MB-231 Cells by Glycoprotein from Codium decorticatum

Abstract: Marine macroalgae consist of a range of bioactive molecules exhibiting different biological activities, and many of these properties are attributed to sulfated polysaccharides, fucoxanthin, phycobiliproteins, and halogenated compounds. In this study, a glycoprotein (GLP) with a molecular mass of ∼48 kDa was extracted and purified from Codium decorticatum and investigated for its cytotoxic properties against human MDA-MB-231 breast cancer cells. The IC₅₀ values of GLP against MDA-MB-231 and normal breast HBL-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 44 publications
1
48
0
Order By: Relevance
“…These data indicate that ROS play an upstream role of caspase, AIF, Endo G and RIPK1 in SHK-induced apoptosis. ROS typically promote mitochondrial dysfunction and mitochondria-mediated apoptosis424344. We consider that ROS play an upstream role and mediate mitochondria-related apoptosis in gastric cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…These data indicate that ROS play an upstream role of caspase, AIF, Endo G and RIPK1 in SHK-induced apoptosis. ROS typically promote mitochondrial dysfunction and mitochondria-mediated apoptosis424344. We consider that ROS play an upstream role and mediate mitochondria-related apoptosis in gastric cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, in both European Society of Urogenital Radiology and the Kidney Disease: Improving Global Outcomes guidelines, either IOCM or LOCM was recommended in patients with increased risk of CI-AKI [28, 29]. Mounting evidence demonstrated that ROS generation and mitochondrial membrane depolarization may lead to DNA damage and apoptosis [30, 31]. Recent studies indicated that an excess generation of mitochondrial ROS played an important role in the pathogenesis of AKI [32, 33].…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle arrest was found from fractions of one green alga (COD), two red algae (PEY1 and PEY2), as well as from the two species of the brown algal genus Cystoseira (CYS1 and CYS2). Cell cycle arrest in G2/M or the induction of apoptosis has been described from a glycoprotein of Codium decoraticum [45] as well as a cholesterol derivative from Codium sp. [42].…”
Section: Discussionmentioning
confidence: 99%